ANALISIS ASAM LEMAK TIDAK JENUH DALAM MINYAK BIJI KENARI (CANARIUM INDICUM L.) HASIL PENGEMPAAN HIDRAULIK - Arnold
Canarium is one of the original plant in Eastern Indonesia and it grows largely in Northen Maluku. It has not became main priority of agricultural and it is used only as complementary food. But actually, it has many nutritions and the oil has a lot of benefit for health. Canarium seed oil contains various fatty acid compounds, one of them is unsaturated fatty acid, like oleic acid. Fatty acids have benefits in medical world, as prevention and cure some diseases. This research purpose was to determine fatty acid concentration and validate the method of determination oleic acid in canarium seed oil sample obtained by hydraulic pressing. The sample preparation steps were started with extraction using pressing method with Hydraulic — Pressure Test Machine at 30°C and 400 psi pressure for 10 minutes, esterification with methanol and sulfic acid as acid catalyst, up to the measurement oleic acid levels using gas chromatography elution programmed system at initial temperature 185°C for 15 minutes, OV-1 capillary column (25 m x 0.53 mm), nitrogen gas, Flame Ionization Detector at 280°C, and the injector at 250°C. In canarium seed oil sample contained saturated fatty acids, which are palmitic acid and stearic acid, and also unsaturated fatty acid, which is oleic acid. Optimized condition was resulted at a column temperature of 185°C for 15 minute, the injector and detector were kept at 250°C and 280°C. The result of validation showed a coefficient of correlation (r) was 0.999; coefficient variancy (V°) of 1.882%; limit of detection (LOD) of 65.211 ligitnL; and limit of quantization (LOQ) of 197.609 p.g/mL. Intraday precision revealed a coefficient of variance of 1.09% and interday precision revealed a coefficient of variance of 1.17%. Accuracy test resulted a percentage of recovery in a range of 100.73-101.56%. Concentration of oleic acid, stearic acid, and palmitic acidwere 50.65%, 11.40%, and 23.58% respectively. The gas chromatography condition in analysis method could be used to determine concentration of oleic acid in canarium seed oil.